2006
DOI: 10.1039/b606205a
|View full text |Cite
|
Sign up to set email alerts
|

On determining the nuclearity of iron sites in Fe-ZSM-5—a critical evaluation

Abstract: In order to interpret catalytic data on iron zeolites in terms of structure-activity relationships, reliable characterisation methods are needed. In particular, the nuclearity of the iron species is an important issue, since it is often invoked to explain catalytic activity. In the present contribution, we address the problem of the nuclearity of the iron species in Fe-ZSM-5 by a combination of techniques, that is, UV-Vis, EXAFS, Magnetic Circular Dichroism (MCD) and magnetisation measurements. Based on an in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 70 publications
6
88
0
Order By: Relevance
“…This process is followed by atomic oxygen migration which occurs through the highest free energy barrier. This result suggested that the latter process (reaction (5)) is the rate determining step of the overall kinetics. The catalyst is regenerated after a-oxygen recombination and molecular oxygen desorption.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…This process is followed by atomic oxygen migration which occurs through the highest free energy barrier. This result suggested that the latter process (reaction (5)) is the rate determining step of the overall kinetics. The catalyst is regenerated after a-oxygen recombination and molecular oxygen desorption.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, the reaction rate increases in time and this autocatalytic effect is assigned to the accumulation of NO x surface species. 5,11,25 Its formation comes from the interaction between N 2 O and the atomic a-oxygen labeled as (O) Fe (reaction (9)). …”
Section: Reaction Order Under Steady-state Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Binuclear Fe species bound to framework Al as well as isolated Fe species associated with framework or extra-framework Al have been proposed as the active sites for benzene hydroxylation. 8,10,17 Raman spectroscopy is useful in the study of these materials because the vibrational modes of oxo/hydroxobridged metal sites are readily observed. 18 XAFS has also proven to be a powerful tool for establishing the connectivity of the Fe species present in Fe/ZSM-5.…”
mentioning
confidence: 99%
“…8,9 Fe may be present inside the zeolite as mono-, bi-, or oligo-nuclear species, iron oxide clusters in varying degrees of agglomeration, mixed-oxide phases containing both Fe and Al, as well as bulk iron oxides on the external surfaces of the zeolite. [9][10][11][12][13] The preparation and pretreatment of the catalyst can affect the distribution and even the nature of the Fe sites. As a result of this heterogeneity, the species responsible for the unique catalytic activity of Fe/ZSM-5 remains elusive.…”
mentioning
confidence: 99%